IMPLEMENTASI TIME DRIVER ABC (TDABC) DALAM PERHITUNGAN HARGA POKOK PRODUKSI AMDK MERK “RIO” - Bayangkara, IBK (Universitas 17 Agustus 1945 Surabaya, 2019)
ABSTRACTThe purpose of this study is to examine the applicability of Time Driver Activity Bassed Costing (TDABC) in the calculation of the cost of production at manufacturing companies. A qualitative research design with a case study approach has been carried out on the production of RIO bottled drinking water (AMDK), a business unit of the BUMN Employees Cooperative in Gresik, for this test. Time drivers have provided solutions to the difficulty of implementing the ABC method in calculating the cost of production, due to the diversity of activity drivers. TDABC does not change the ABC method as a whole, but only simplifies the determination of activity drivers by time drivers. TDABC which is applied in the calculation of the cost of goods manufactured at a manufacturing company can produce a cost calculation of production costs that is more accurate than the calculation of the cost of production using the traditional method, because it has distributed overhead costs to each product based on the activity consumed by the product measured in units of time . More further research is needed on the application of TDABC in manufacturing companies, so that the difficulties of applying this method can be identified and solutions can be found. Keywords: TDABC, calculation, manufacturing, accurate.